Given the equation:
![y=x^2-x-6](https://tex.z-dn.net/?f=y%3Dx%5E2-x-6)
Let's find the x-intercepts and the y-intercepts of the graph.
• x-intercept:
The x-intercept are the points where the parabola crosses the x-axis. At x-intercept the y-value is zero.
To find the x-intercepts, substitute 0 for y and solve for x.
We have:
![0=x^2-x-6](https://tex.z-dn.net/?f=0%3Dx%5E2-x-6)
Rewrite the equation:
![x^2-x-6=0](https://tex.z-dn.net/?f=x%5E2-x-6%3D0)
Factor the left hand side of the equation:
![(x-3)(x+2)=0](https://tex.z-dn.net/?f=%28x-3%29%28x%2B2%29%3D0)
Equate each factor to zero:
x - 3 = 0
Add 3 to both sides:
x - 3 + 3 = 0 + 3
x = 3
x + 2 = 0
Subtract 2 from both sides:
x + 2 - 2 = 0 - 2
x = -2
Therefore, the x-intercepts are:
3, -2
• y-intercept:
The y-intercept is the point where the parabola crosses the y-axis. The x-value at the y-intercept is zero.
To find the y-intercept, substitute 0 for x and solve:
![\begin{gathered} y=0^2-0-6 \\ \\ y=-6 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20y%3D0%5E2-0-6%20%5C%5C%20%20%5C%5C%20y%3D-6%20%5Cend%7Bgathered%7D)
Therefore, the y-intercept is -6.
In point form:
x-intercept: (3, 0), (-2, 0)
y-intercept: (0, -6)
ANSWER:
A. The x-intercepts are (3, 0), (-2, 0)
A. The y-intercept is (0, -6)